Energy Consumption Optimization in Hard Real-Time System CMOS Processors - Baums, A. (Elektronika ir Elektrotechnika, 2006)
Energy consumption reduction is of primary importance in mobile embedded systems and SoC design. Dynamic voltage scaling (DVS) for CMOS chips is the most effective energy reduction technology. For hard real–time system optimisation DVS based task online scheduling method “mini-max” was developed. By it using the deadline is guaranteed at the task execution at minimal power till critical time, after which task is finished at maximal clock frequency and speed. In paper the benefits of the mini-max method using for energy saving is estimated and the optimal frequency selection for hard deadline task execution is analysed. Ill. 7, bibl. 16 (in English; summaries in English, Russian and Lithuanian).